The United States proscription of Hezbollah: a critical discourse analysis (1985-1997) - Cheaito, Karime Ahmad Borraschi [UNESP] (Critical Studies on Terrorism, 2026)
Hezbollah, a Lebanese political and armed organisation founded in 1982, was designated a Foreign Terrorist Organization (FTO) by the United States. Since then, the US has pressured other states to adopt similar designations, producing significant material and symbolic consequences, particularly for the Lebanese diaspora. This research examines the accusations and motivations underlying Hezbollah’s designation as a terrorist organisation. It argues that, rather than simply seeking to delegitimize Hezbollah, the proscription primarily aimed to reinforce containment strategies against Iran, viewed as a key challenger to US and Israeli strategic interests in the Middle East. Grounded in Critical Security Studies (CSS) and Critical Terrorism Studies (CTS), the study adopts a qualitative methodology that combines case study analysis with critical discourse analysis of US official documents and presidential speeches from 1985 to 1997. The findings suggest that Hezbollah’s designation was not an isolated response to security concerns but part of a broader political strategy to advance US regional interests. As such, the case provides insights into wider Middle Eastern power dynamics, highlighting how terrorism designations can function as political instruments in the pursuit of regional security agendas.
A proibição do Hezbollah pelos Estados Unidos: uma análise crítica do discurso (1985-1997)
Keywords: Hezbollah; United States; Proscription; Critical Terrorism Studies